Beginning C++ through game programming - Dawson, Mike, 1947- (Boston : Cengage Learning, 2015)
When it comes to game programming, C++ is the name of the game. If you aspire to move from game player to game creator, it all starts with learning the fundamentals of C++ and game-programming basics. With BEGINNING C++ THROUGH GAME PROGRAMMING, FOURTH EDITION, you will find an up-to-date and thorough introduction to everything you need to get started—with no previous programming experience required. In the new fourth edition of this popular guide to learning C++, you will work with a complete program while learning each new concept and a game program at the end of each chapter. A final game project at the end of the book draws together everything you've learned.
"Cengage Learning PTR."
Includes index.
Keywords: Computer games -- Programming; C++ (Computer program language).